2016
DOI: 10.1080/17453674.2016.1253327
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-bearing medial unicompartmental knee arthroplasty restores limb alignment comparable to that of the unaffected contralateral limb

Abstract: Background and purpose — Medial unicompartmental knee arthroplasty (UKA) is undertaken in patients with a passively correctable varus deformity. We investigated whether restoration of natural soft tissue tension would result in a lower limb alignment similar to that of the contralateral unaffected lower limb after mobile-bearing medial UKA.Patients and methods — In this retrospective study, hip-knee-ankle (HKA) angle, position of the weight-bearing axis (WBA), and knee joint line obliquity (KJLO) after mobile-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Many authors have reported that the MB design has a theoretical advantage over the FB design and offers better restoration of natural kinematics of the knee. [31][32][33] Some other studies have shown similar functional outcomes and ROM of the MB and FB designs. 14,30 Our meta-analysis Abbreviation: RCT, randomized controlled trial.…”
Section: Discussionmentioning
confidence: 71%
“…Many authors have reported that the MB design has a theoretical advantage over the FB design and offers better restoration of natural kinematics of the knee. [31][32][33] Some other studies have shown similar functional outcomes and ROM of the MB and FB designs. 14,30 Our meta-analysis Abbreviation: RCT, randomized controlled trial.…”
Section: Discussionmentioning
confidence: 71%
“…2) and in the surgical techniques required for their implantation. The MB is designed to allow more natural joint kinematics [98,99], while also allowing a higher degree of conformity between the articular surfaces. Its distinctive design is proposed to reduce the surface and subsurface contact stresses granting less likelihood of polyethylene wear compared with FB designs [100,101].…”
Section: Choice Of Bearing Design: Mobile or Fixed Bearing?mentioning
confidence: 99%
“…In orthopedics, alignment of the contralateral side is often referenced to help establish a surgical plan and parameters for evaluating radiographic correction. 3,7,24,32,34 Our hypothesis was based on the principle that both feet were symmetrically aligned before the Kidner procedure. Radiographically, both sides had similar deformity, with 14 patients (67%) having identical alignment.…”
Section: Discussionmentioning
confidence: 99%